Leishmania amazonensis Promastigotes or Extracellular Vesicles Modulate B-1 Cell Activation and Differentiation - Reis, Natasha Ferraz de Campos; Dupin, Talita Vieira; Costa, Carolina Rizzaro; Toledo, Maytê dos Santos; de Oliveira, Vivian Cristina; Popi, Ana Flavia; Torrecilhas, Ana Claudia; Xander, Patricia (Frontiers in Cellular and Infection Microbiology, 2020)
B-1 cells are considered an innate-like B cell population that participates in effective innate and adaptive responses to pathogens. B-1 cells produce immunoglobulins, cytokines, chemokines, migrate to inflammatory sites, and differentiate into mononuclear phagocyte-like cells. Murine B-1 cells phagocytosed Leishmaniain vitro and in vivo and participate in immunity against Leishmania. Our group showed that B-1 cells or their extracellular vesicles (EVs) led to a resistance to experimental infection by L. amazonensis. However, the B-1 cells’ responses to Leishmania or EVs isolated from parasites are still poorly characterized. Studying the activation and differentiation of B-1 cells in vivo can contribute to a better understanding of how these cells participate in immunity to L. amazonensis. Thus, we evaluated the expression of myeloid (M-csfr, G-csfr, Spi-1) and lymphoid (EBF, E2A, IL-7R) lineage commitment factors, Toll-like receptors (TLRs), activation cell surface markers, nitric oxide (NO) and reactive oxygen species (ROS) production in murine peritoneal B-1 cells collected after 24 or 48 h post-infection with Leishmania (Leishmania) amazonensis promastigotes or EVs released by the parasites. Our results demonstrated that L. amazonensis infection did not stimulate the expression of CD40, CD80, CD86, F4/80, and MHC II in B-1 cells, but a significant decrease in the production of NO and ROS was observed. The infection induced a significantly higher arginase expression in B-1 cells, but the stimulation with EVs led to a decrease in this gene expression. TLR-2 and TLR-6 had significantly higher expression in B-1 cells from mice intraperitoneally stimulated with the parasite. The TLR-9 expression was higher in animals infected or stimulated for 48 h with EVs. Interestingly, in B-1 cells the stimulus with L. amazonensis led to a substantial increase in the expression of myeloid restricted transcription factors. Thus, our study suggests that the parasites or EVs differently modulated the activation and differentiation of B-1 cells.